Using LEGO® SERIOUS® Play with stakeholders for RRI - Stevienna de Saille; Alice Greenwood; James Law; Mark Ball; Mark Levine; Elvira Perez Vallejos; Cath Ritchie; David Cameron (Journal of Responsible Technology, 2022)
This paper discusses Responsible (Research and) Innovation (RRI) within a UKRI project funded through the Trustworthy Autonomous Systems Hub, Imagining Robotic Care: Identifying conflict and confluence in stakeholder imaginaries of autonomous care systems. We used LEGO® Serious Play® as an RRI methodology for focus group workshops exploring sociotechnical imaginaries about how robots should (or should not) be incorporated into the existing UK health-social care system held by care system stakeholders, users and general publics. We outline the workshops’ protocol and some emerging insights from early data collection, including the ways that LSP aids in the surfacing of tacit knowledge, allowing participants to develop their own scenarios and definitions of ‘robot’ and ‘care’. We further discuss the implications of LSP as a method for upstream stakeholder engagement in general and how this may contribute to embedding RRI in robotics research on a larger scale.